Prognostic value of soluble ST2 in AL and TTR cardiac amyloidosis: a multicenter study - Nicol, Martin; Vergaro, Giuseppe; Damy, Thibaud; Kharoubi, Mounira; Baudet, Mathilde; Canuti, Elena Sofia; Aimo, Alberto; Castiglione, Vincenzo; Emdin, Michele; Royer, Bruno; Harel, Stephanie; Cohen-Solal, Alain; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Both light-chain (AL) amyloidosis and transthyretin (ATTR) amyloidosis are types of cardiac amyloidosis (CA) that require accurate prognostic stratification to plan therapeutic strategies and follow-ups. Cardiac biomarkers, e.g., N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin T (Hs-cTnT), remain the cornerstone of the prognostic assessment. An increased level of soluble suppression of tumorigenesis-2 (sST2) is predictive of adverse events [all-cause death and heart failure (HF) hospitalizations] in patients with HF. This study aimed to evaluate the prognostic value of circulating sST2 levels in AL-CA and ATTR-CA. Methods We carried out a multicenter study including 133 patients with AL-CA and 152 patients with ATTR-CA. During an elective outpatient visit for the diagnosis of CA, Mayo Clinic staging [NT-proBNP, Hs-cTnT, differential of free light chains (DFLCs)] and sST2 were assessed for all AL patients. Gillmore staging [including estimated glomerular filtration rate (eGFR), NT-proBNP] and Grogan staging (including NT-proBNP and Hs-cTnT) were assessed for TTR-CA patients. Results The median age was 73 years [interquartile range (IQR) 61–81], and 53% were men. The endpoint was the composite of all-cause death or first HF-related hospitalization. The median follow-up was 20 months (IQR 3–34) in AL amyloidosis and 33 months (6–45) in TTR amyloidosis. The primary outcome occurred in 70 (53%) and 99 (65%) of AL and TTR patients, respectively. sST2 levels were higher in patients with AL-CA than in patients with ATTR-CA: 39 ng/L (26–80) vs. 32 ng/L (21–46), p < 0.001. In AL-CA, sST2 levels predicted the outcome regardless of the Mayo Clinic score (HR: 2.16, 95% CI: 1.17–3.99, p < 0.001). In TTR-CA, sST2 was not predictive of the outcome in multivariate models, including Gillmore staging and Grogan staging (HR: 1.17, CI: 95% 0.77–1.89, p = 0.55). Conclusion sST2 level is a relevant predictor of death and HF hospitalization in AL cardiac amyloidosis and adds prognostic stratification on top of NT-proBNP, Hs cTnT, and DFLC.